2016
DOI: 10.1124/dmd.116.070367
|View full text |Cite
|
Sign up to set email alerts
|

A New Marmoset P450 4F12 Enzyme Expressed in Small Intestines and Livers Efficiently Metabolizes Antihistaminic Drug Ebastine

Abstract: Common marmosets (Callithrix jacchus) are attracting attention as animal models in preclinical studies for drug development. However, cytochrome P450s (P450s), major drug-metabolizing enzymes, have not been fully identified and characterized in marmosets. In this study, based on the four novel P450 4F genes found on the marmoset genome, we successfully isolated P450 4F2, 4F3B, 4F11, and 4F12 cDNAs in marmoset livers. Deduced amino acid sequences of the four marmoset P450 4F forms exhibited high sequence identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…On the other hand, both marmoset P450 4F12 and cynomolgus monkey P450 4F12, expressed in small intestines and livers, more efficiently metabolized ebastine oxidation than marmoset and monkey P450 2J2 did [33]. These findings indicated that some marmoset or cynomolgus monkey P450 enzymes had apparently different functional characteristics to those of humans.…”
Section: Marmosetcontrasting
confidence: 45%
“…On the other hand, both marmoset P450 4F12 and cynomolgus monkey P450 4F12, expressed in small intestines and livers, more efficiently metabolized ebastine oxidation than marmoset and monkey P450 2J2 did [33]. These findings indicated that some marmoset or cynomolgus monkey P450 enzymes had apparently different functional characteristics to those of humans.…”
Section: Marmosetcontrasting
confidence: 45%
“…Non-human primates can be classified into old-world and new-world monkeys [29]; the marmoset belongs to the class of new-world monkeys. Their features and application to various biomedical research studies have been mainly conducted in Japan, and recently, the wider usage of marmoset as a model is emerging [23,30,31,32,33,34]. From the perspective of reproductive physiology, non-human primates are closely related to human models; however, due to the high cost of the supply and maintenance of marmosets, a limited number of researchers are using this NHP model.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 36 C. jacchus CYP isoenzymes (cjCYP) have been identified and 24 of them, belonging to 1A, 2A, 2B, 2C, 2D, 2E, 3A, 4A, and 4F subfamilies, share a high degree of homology in the cDNA (>89%) and amino acid sequences (>85%) with corresponding human P450s [ 180 ]. Among these, CYP1A2, 2A6, 2B6, four 2C subfamily members (2C8, 2C18, 2C19 and 2C58), 2D6, 2D8, 2E1, 2J2, 3A4, 3A5, 4A11, 4F2, 4F12 and 7B1 are expressed in the marmoset liver [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 ]. Interestingly, CYP1D1 , encoded by a pseudogene in human liver is also pseudogenized in C. jacchus due to an incomplete open reading frame [ 180 ].…”
Section: Drug Metabolism Studies With Marmoset Esc-derived Hlcsmentioning
confidence: 99%